Double trouble: unit specific counselling for mode of delivery of twin pregnancy. (7th June 2011) - Higgins, L; Gupta, S; Gillham, J
Abstract : Introduction: The incidence of multiple pregnancy is rising in the UK. The safest mode of delivery for twin pregnancies is not known. Method: Case note review of 294/324 (90.74%) twin deliveries occurring at a teaching hospital in Manchester 1 July 2007–1 July 2010 considered mode of delivery, cord acidaemia, neonatal unit admission (NNU)) and postpartum haemorrhage (PPH). Baseline characteristics: (table 1 ). Mode of delivery: 55.44% of women (34.36% of those aiming for VD) deliver at least one twin by CS; risk factors include nulliparity, previous CS and gestational age <34 weeks (p<0.05). 6.43% of women achieving VD of twin one (T1) deliver twin two (T2) by CS. Morbidity: Fetal cord acidaemia occurred in 40.88% of deliveries (T2 more frequent than T1, p<0.05). T2 acidaemia was not associated with instrumental versus CS T2 delivery or cephalic versus breech T2 VD (p<0.05). Cord arterial pH was negatively associated with delivery interval (p<0.05). Admission to NNU followed 40.56% of twin deliveries; risk factors include T2 breech VDs >34 weeks and deliveries 34 to 36+6 weeks (p<0.05). 45.05% of women experienced PPH; risk factors include nulliparity, previous CS, syntocinon infusion >1 h and CS delivery of either twin (p<0.05). Discussion: The results of the Twin Birth Study are awaited. Examining unit specific figures aids patient counselling and clinician decision making to promote optimal perinatal outcomes.